'Cotton-ball' shaped porous iron-nickel sulfide: A high-rate cathode for long-life aqueous rechargeable battery. (August 2021) - Pramanik, Atin; Maiti, Sandipan; Chattopadhyay, Shreyasi; De, Goutam; Mahanty, Sourindra
Graphical abstract: Highlights: Synthesis of porous FeNi2 S4 'cotton-ball' like morphology by hydrothermal technique. First report of FeNi2 S4 //AC aqueous rechargeable battery. High energy density of ∼215.7 W h kg −1 at a power density of ∼1184.5 kW kg −1 . Excellent cycling stability (∼87 % of capacity retention after 10, 000 cycles). Abstract: Aqueous rechargeable batteries (ARB) offer reasonably higher energy density and cycle life than their non-aqueous counterparts. Yet, the bottleneck is a limited choice of positive electrodes coupled with low-rate capability and inadequate cycle life. We report here a wet chemical approach to synthesize in-situ three-dimensional (3D) 'cotton-ball' shaped porous iron-nickel sulfide (FeNi2 S4 ) (henceforth referred to as PINS) as a diffusion-controlled ARB electrode. It shows a high specific capacity of 177 mA h g −1 at 1 A g −1 vs Pt in the alkaline electrolyte with excellent rate capability (89 mA h g −1 at 40 A g −1 ) and ultra-long cycle life (10, 000 cycles). Furthermore, a pouch-type full-cell ARB (FeNi2 S4 //AC) delivers an energy density of 56.7 Wh kg −1 at a power density of 871.5 W kg −1 with high cycling stability (10, 000 cycles). The present study offers a straightforward and efficient approach for developing nanostructured transition metal sulfide-based cathode materials for practical ARB.